2019
DOI: 10.1016/j.celrep.2019.02.111
|View full text |Cite
|
Sign up to set email alerts
|

PI3K Inhibition Activates SGK1 via a Feedback Loop to Promote Chromatin-Based Regulation of ER-Dependent Gene Expression

Abstract: SUMMARY The PI3K pathway integrates extracellular stimuli to phosphorylate effectors such as AKT and serum-and-glucocorticoid-regulated kinase (SGK1). We have previously reported that the PI3K pathway regulates estrogen receptor (ER)-dependent transcription in breast cancer through the phosphorylation of the lysine methyltransferase KMT2D by AKT. Here, we show that PI3Kα inhibition, via a negative-feedback loop, activates SGK1 to promote chromatin-based regulation of ER-dependent transcription. PI3K/AKT inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 50 publications
(88 reference statements)
0
57
1
Order By: Relevance
“…Thus, a negative feedback loop activates SGK1 to promote chromatin-based regulation of ER-dependent gene expression (Figure 2). Given that high levels of active SGK1 would inhibit ER activity making cells less dependent on the ER response [47], we speculate that SGK1 could be another important mediator of resistance not only to PI3K inhibitors, as we have previously reported [33], but also to endocrine therapies. Other hormone nuclear receptors such as PR or retinoic acid receptor [48, 49] have been previously linked to affect ER transcriptional activity, and their gene signatures are elevated by PI3K kinase inhibition [46].…”
Section: Crosstalk Between Er and Pi3k Pathwaymentioning
confidence: 78%
“…Thus, a negative feedback loop activates SGK1 to promote chromatin-based regulation of ER-dependent gene expression (Figure 2). Given that high levels of active SGK1 would inhibit ER activity making cells less dependent on the ER response [47], we speculate that SGK1 could be another important mediator of resistance not only to PI3K inhibitors, as we have previously reported [33], but also to endocrine therapies. Other hormone nuclear receptors such as PR or retinoic acid receptor [48, 49] have been previously linked to affect ER transcriptional activity, and their gene signatures are elevated by PI3K kinase inhibition [46].…”
Section: Crosstalk Between Er and Pi3k Pathwaymentioning
confidence: 78%
“…elevated SGK's may be a biomarker of resistance to the concomitant inhibition of PI3K and ER. 10 Moreover, our observations provide mechanistic understanding of ER regulation by the PI3K signaling and underscore the relevance of the chromatin state in connecting the oncogenic signaling responses with gene activity. (A) AKT1 (also known as protein kinase B, PKB), phosphorylates the H3K4 histone lysine methyltransferase KMT2D at S1331 and negatively regulates its activity leading to a repression of ER, FOXA1 (Forkhead Box A1), and PBX1 (PBX Homeobox 1) transcriptional regulatory network recruitment and attenuation of ER-dependent transcription (AKT1-dependent mechanism).…”
mentioning
confidence: 67%
“…In summary, we and others have highlighted the importance of elucidating the overlooked role of SGK's in cancer and therapy response. [8][9][10] For instance, previous studies have shown SGK's to be an important mediator of resistance to PI3K inhibitors 8,9 and, in our recent work, we speculate that a b Figure 1. AKT1 and SGK1-dependent mechanism/s of estrogen receptor (ER) regulation by KMT2D.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…mTORC2 exerts its epigenetic function by activation of the AKT and SGK1 proteins. The effect of these proteins on epigenetic regulation is the inhibition of KMT2D, which is a histone methyltransferase specifically targeting H3K4 (Figure 2) (43). Inhibition of KMT2D has been shown to have anti-tumor effects in some cancers by not allowing the FOXA1-PBX-ER complex to access the DNA for transcription (44).…”
Section: Heritable Epigenetic Modifications Acquired Through Microenvmentioning
confidence: 99%